Fabrication and characterisation of super‐paramagnetic responsive PLGA–gelatine–magnetite scaffolds with the unidirectional porous structure: a physicochemical, mechanical, and in vitro evaluation - Farnaz Ghorbani; Ali Zamanian; Alireza Shams; Atefeh Shamoosi; Amir Aidun (IET Nanobiotechnology)
Architecture and composition of Scaffolds are influential factors in the regeneration of defects. Herein, synthesised iron oxide (magnetite) nanoparticles (MNPs) by co‐precipitation technique were evenly distributed in polylactic‐co‐glycolic acid (PLGA)–gelatine Scaffolds. Hybrid structures were fabricated by freeze‐casting method to the creation of a matrix with tunable pores. The synthesised MNPs were characterised by transmission electron microscopy, Fourier transform infrared spectroscopy, X‐ray diffraction spectroscopy, and vibrating sample magnetometer analysis. Scanning electron microscopy micrographs of porous Scaffolds confirmed the formation of unidirectional microstructure, so that pore size measurement indicated the orientation of pores in the direction of solvent solidification. The addition of MNPs to the PLGA–gelatine Scaffolds had no particular effect on the morphology of the pores, but reduced slightly pore size distribution. The MNPs contained constructs demonstrated increased mechanical strength, but a reduced absorption capacity and biodegradation ratio. Stability of the MNPs and lack of iron release was the point of strength in this investigation and were determined by atomic absorption spectroscopy. The evolution of rat bone marrow mesenchymal stem cells performance on the hybrid structure under a static magnetic field indicated the potential of super‐paramagnetic constructs for further pre‐clinical and clinical studies in the field of neural regeneration.